The Bad Guys in they're bee-hind you! - Blabey, Aaron (Blabey, Aaron. Bad guys, 2021)
"Pop quiz! You are on the roof of a skyscraper. Every floor of that building has nasty things that just don't like you. And you really need to get to the basement. Whaddaya do?! (And no, you can't just join the B-Team and fly away in their glamorous new spaceship.) Think quick, chico, because the multiverse is getting worse!"--Provided by publisher.